Partisipasi Masyarakat Dalam Program Penyedian Air Minum Dan Sanitasi Berbasis Masyarakat (PAMSIMAS) Di Desa Jandiraya Kecamatan Dolog Masagal Kabupaten Simalungun - Yuki Sonia Purba; Siti Hazzah Nur. R (UNIVED PRESS, Universitas Dehasen Bengkulu, 2022)
This study aims to analyze community participation in the PAMSIMAS community-based water supply and sanitation program in Jandiraya Village, Dolog Masagal District and to describe research on PAMSIMAS and analyze community problems regarding the need for clean water in Jandiraya Village, Dolog Masagal District, Simalungun Regency. The method used is descriptive qualitative research method through data collection such as interviews, observation, documentation, and literature studies. The results of field research concluded that community participation in the PAMSIMAS provision program had been completed so that there were real results from PAMSIMAS development. Community participation in development has been quite good, as seen by the community still carrying out PAMSIMAS development so that construction is complete. It's just that the level of community participation is still relatively low so that it is not optimal in carrying out this PAMSIMAS development. This lack of community participation is due to the work done by the Jandiraya village community to meet the needs of the village community.